Prevalence of musculoskeletal pain among undergraduate students - Kandasamy, Geetha; Almanasef, Mona; Almeleebia, Tahani; Orayj, Khalid; Shorog, Eman; Alshahrani, Asma M.; Prabahar, Kousalya; Veeramani, Vinoth Prabhu; Amirthalingam, Palanisamy; Alqifari, Saleh F.; Alrashidi, Fayez; Aldurum, Muteb; et al. (Frontiers in Medicine, 2024)
Introduction Musculoskeletal disorders (MSDs) are rapidly rising in Saudi Arabia, reaching levels similar to those in the Western world. Hence, we aimed to assess the prevalence of neck, shoulder, and lower back pains (musculoskeletal pain, MSP) among students at King Khalid University in Abha, Saudi Arabia. Methods This cross-sectional study was conducted at King Khalid University in Abha, Saudi Arabia, from March 2023 to August 2023. Inclusion criteria were: university students aged 18 years and older of both sexes who agreed to participate in the study. The modified Nordic questionnaire was used, which comprised three parts. Results Out of 536 respondents, 337 were women and 199 were men. The average body mass index (BMI) of the study population was 25.3 ± 4.01. In total, 223 (41.60%) had a history of MSDs. Only 232 (43.28%) of the population did regular exercise. According to multiple logistic regression analysis, factors associated with MSDs are mobile device use (with both hands) with a large neck tilt below the horizon line position (OR = 2.276, CI 1.178–4.397, p = 0.014), family history of trauma (OR = 5.450, 95% CI 3.371–8.811, p = 0.000), family history of MSDs (OR = 4.241, 95% CI 2.296–7.835, p = 0.000), coffee consumption (OR = 1.967, CI 1.281–3.020, p = 0.002), and time spent on electronic devices: 1–3 h (OR = 0.252, 95% CI 0.124–0.511, p = 0.0001), 4–6 h (OR = 0.455, 95% CI 0.237–0.873, p = 0.018), and 6–9 h (OR = 0.348, 95% CI 0.184–0.660, p = 0.001). Conclusion The present study concludes that MSP among university students is high. A history of trauma, a family history of MSDs, the hand and neck position when using electronic devices, the amount of time spent using them, and regular exercise are risk factors that are strongly associated with MSP. There is strong evidence to suggest that increasing physical activity plays a significant role in enhancing the functionality of the musculoskeletal (MSK) system and alleviating pain. It is recommended that universities implement educational programs to raise awareness and health screenings about the impact of device usage on MSK health and the benefits of regular exercise.